The failures and possibilities of philosophy in the material world - Van Cleave, Jessica; Marn, Travis; Wolgemuth, Jennifer (International Review of Qualitative Research, 2025)
Keywords: Engineering; Engineering ethics; Epistemology; Philosophy; dept.cur

Manufacturing Trustworthiness in Qualitative Research as a Writerly and Readerly Accomplishment: Introduction to the Special Issue - Van Cleave, Jessica; Wolgemuth, Jennifer; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Construct (python library); Product (mathematics); Qualitative research; Space (punctuation); Theme (computing); Tinker; Trustworthiness; dept.cur; possibility; publication; scholarly writing; trustworthiness

#scholar #famous #monster - Wolgemuth, Jennifer; Lester, Jessica; Guyotte, Kelly; Koro‐Ljungberg, Mirka; Marn, Travis (Educational Researcher, 2025)
Academic success is now coupled with social media engagement. Social media has become so normalized in the academy that absent a carefully curated social media presence, scholars risk being seen as unscholarly, unproductive, and unpopular. This article lays bare the pressures, mechanisms, and monstrosities of using social media to promote scholarship. We argue that the widespread adoption of social media outpaces critical attention to its ethics and wonder about the future of public scholarship and the monstrous scholarly selves we are becoming. Thinking of monstrosity, with Krecˇicˇ and Žižek, as the preontological domain that rests beneath society and constitutes alterity and otherness, we ask what kinds of #scholarfamousmonsters we want to be, become, and promote in the digital era.
Keywords: Aesthetics; Art; Epistemology; Law; Literature; Media studies; Monster; Philosophy; Political science; Psychology; Scholarship; Social media; Social psychology; Sociology; Wonder; dept.cur; peer-reviewed